Imagens de fé : uma busca de critérios na produção de subsídios audiovisuais para o ensino religioso no Brasil - Pacheco, Luis Carlos de Lima (2011)
This research aims at developing criteria for subsidies through video production for Religious Education, in the Brazilian schools. It arises from the fact that there is an unfilled gap in Religious Education regarding to audiovisual subsidies, concerning the content, to new Educational Policy implementation and its interreligiousety demands and respect to human dignity, as well as that they would attend, on terms of form, to nowadays electronic culture. This Paper therefore presents the Religious Education historiography, in Brazil, and draws up the Brazilian Religious Field, which from one provides a legal curricular stand-platform for Religious Education subsidies evaluation that ought to become an indispensable theme knowledge, as a cultural experience regarding to transcendence. Thereupon, we will deep the epistemological foundations in order to analyze the Religious Education audiovisual subsidies: Pierre Babin s media theory on Modulation and approaches concerning Transdisciplinary and Integral Knowledge (Barsarab Nicolescu and Ken Wilber). Then, based upon this historical and epistemological support, we fulfill criteriology text, departing from an exemplary audiovisual work, in the School Religious Education